1974
DOI: 10.2337/diab.23.3.221
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Accumulation in Retinal Neurons and Glial Cells of Streptozotocin-diabetic Rats: Quantitative Electron Microscopy

Abstract: The concentration of glycogen |3-particles was measured in the inner retinal layers of normal and streptozotocin-diabetic rats with quantitative electron microscopic technics. Diabetes was uncontrolled and of short duration (thirty days). Blood glucose levels in the normal and diabetic animals were 76 ± 8 S.E. and 340 ± 25 S.E. mg./lOO ml. Diabetes caused glycogen accumulation in the amacrine, bipolar, ganglionic, Miiller and capillary mural cells. Quantitative estimates showed significant increases (p < 0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 3 publications
2
9
0
Order By: Relevance
“…The presence of glycogen in retinal neurons, at least in modest amounts has been previously observed by electron microscopy in the amacrine cells of the cat 40 and rat, 31 suggesting that neuronal glycogen deposition per se is not pathologic, and supports recent studies from other parts of the CNS. 13 However, it is likely that the level of glycogen occupancy described above in the perinuclear cytoplasm of the amacrine cells in diabetic rats would eventually disrupt the normal synthetic functions of the endoplasmic reticulum-Golgi complex and downstream transport mechanisms.…”
Section: Glycogen Storage In Retinal Neurons: Pathologic Implicationssupporting
confidence: 70%
See 1 more Smart Citation
“…The presence of glycogen in retinal neurons, at least in modest amounts has been previously observed by electron microscopy in the amacrine cells of the cat 40 and rat, 31 suggesting that neuronal glycogen deposition per se is not pathologic, and supports recent studies from other parts of the CNS. 13 However, it is likely that the level of glycogen occupancy described above in the perinuclear cytoplasm of the amacrine cells in diabetic rats would eventually disrupt the normal synthetic functions of the endoplasmic reticulum-Golgi complex and downstream transport mechanisms.…”
Section: Glycogen Storage In Retinal Neurons: Pathologic Implicationssupporting
confidence: 70%
“…Early studies suggested disturbance of retinal glycogen metabolism during diabetes, [28][29][30] and a small electron microscopic study by Sosula et al 31 showed a disproportionate increase in retinal neurons. However, these observations have been largely overlooked in recent discussion of neuronal dysfunction in diabetic retinopathy, possibly because glycogen is not well retained in current fixation protocols and requires special staining.…”
Section: Glycogen Storage In Diabetic Retinamentioning
confidence: 99%
“…Alteration in endothelial function is already considered a characteristic finding in such disease processes as diabetes mellitus, a pathologic condition characterized by abnormalities of both the secretion of insulin and insulin action. In diabetes, retinal capillary beds demonstrate interendothelial leakage of small proteins, increased transcapillary exchange of plasma fluid components, and endothelial cell proliferation, with each of these findings preceding clinically detectable lesions of the retinal microvasculature (23,24). Our data in the present study now suggest that certain capillary endothelia also serve to control the transcapillary movement of insulin, the hormone central to normal glucose homeostasis.…”
Section: Discussionsupporting
confidence: 58%
“…41 In diabetic animals gross and possibly pathological accumulations of glycogen have been described in retinal amacrine, bipolar and glial cells which reflect sustained supra-normal intraretinal glucose concentrations. 42 Retinal vascular cells also contain scattered glycogen granules, but even in diabetes abnormal deposits are not observed.…”
Section: Glycogen Storagementioning
confidence: 99%